Shared Genetic Factors Influence Head Motion During MRI and Body Mass Index. (15th October 2016) - Hodgson, Karen; Poldrack, Russell A; Curran, Joanne E; Knowles, Emma E; Mathias, Samuel; Göring, Harald HH; Yao, Nailin; Olvera, Rene L; Fox, Peter T; Almasy, Laura; Duggirala, Ravi; Barch, Deanna M; et al.
Abstract: Head movements are typically viewed as a nuisance to functional magnetic resonance imaging (fMRI) analysis, and are particularly problematic for resting state fMRI. However, there is growing evidence that head motion is a behavioral trait with neural and genetic underpinnings. Using data from a large randomly ascertained extended pedigree sample of Mexican Americans ( n = 689), we modeled the genetic structure of head motion during resting state fMRI and its relation to 48 other demographic and behavioral phenotypes. A replication analysis was performed using data from the Human Connectome Project, which uses an extended twin design ( n = 864). In both samples, head motion was significantly heritable ( h 2 = 0.313 and 0.427, respectively), and phenotypically correlated with numerous traits. The most strongly replicated relationship was between head motion and body mass index, which showed evidence of shared genetic influences in both data sets. These results highlight the need to view head motion in fMRI as a complex neurobehavioral trait correlated with a number of other demographic and behavioral phenotypes. Given this, when examining individual differences in functional connectivity, the confounding of head motion with other traits of interest needs to be taken into consideration alongside the critical important of addressing head motion artifacts.